Lily's Dream : A Fairy Friendship - Jackson, Bea, 1986- (New York : Aladdin, 2025)
"Lily is a young fairy determined to learn to fly just like the others who soar on shimmering, jeweled-colored wings, but she's worried her own colorless wings will never lift her off the ground. Then she meets a young girl named Willow who helps her not only discover her special magic, but the truly magical gift of friendship"--
Keywords: African American girls -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Flight -- Juvenile fiction; Friendship in children -- Juvenile fiction; African Americans -- Fiction; Mothers and daughters -- Fiction; Fairies -- Fiction; Magic -- Fiction; Flight -- Fiction; Friendship -- Fiction; Picture books